Registration of Interfaith Marriages According to Positive Law in Indonesia (Analysis of North Jakarta District Court Decision 423/PDT.P/2023/PN JKT.UTR) - Rizki, Rizki; Rajagukguk, Very Harley Aryanto; Junnifer, Junnifer; Winnata, Shareen Angeline (LEGAL BRIEF, 2024)
The practice of marriage according to positive law in Indonesia is regulated by Law Number 1 of 1974 concerning Marriage. Marriage registration at a civil registry office or agency appointed by the government ensures the validity of marriage law and provides the necessary basis for obtaining rights and fulfilling the obligations attached to marital status. Interfaith marriages in Indonesia are not regulated by Law Number 1 of 1974 concerning marriage, this becomes complex because of differences in religious beliefs between the couples who are getting married. One of the cases of a married couple with the initials JEA and SW (which was recorded in the JAKARTA UTARA PN DECISION 423/PDT.P/2023/PN JKT.UTR) faced obstacles when they wanted to register their marriage at the Population and Civil Registry Sub-Department Office (Sudin Disdukcapil) Central Jakarta. The type of research used in this research is normative juridical research. that children resulting from marriages of different religions are illegitimate or illegitimate children. The author fully agrees that the need for additional legal processes, in the form of court decisions, for civil registration of interfaith marriages, is an essential step